The geoarchaeological investigation on the defunctionalisation of an Assyrian canals system reveals Late-Holocene land use transitions in Northern Mesopotamia. (April 2023) - Forti, Luca; Costanzo, Stefano; Compostella, Chiara; Garna, Giancarlo; Morandi Bonacossi, Daniele; Zerboni, Andrea
During the Assyrian rule over Northern Mesopotamia (present-day northern Iraq), complex systems of canals were built to increase the surface of cultivable land and improve the movement of people and goods across the irrigated waterscape of the hinterland of Nineveh and other major urban centres, with the aim of granting socio-economic prosperity to the empire. Nevertheless, supra-regional political instability eventually led to the rapid downfall of the Assyrian state during the late seventh century BCE, causing the swift abandonment of the canal systems. In this study, we examine the post-abandonment formation processes of the natural and anthropogenic infillings of three portions of King Sennacherib's Khinis canal system (705–681 BCE, northwestern Kurdistan Region of Iraq) through means of archaeological, sedimentological and micromorphological analyses. We identify water lain sediments, desiccation features, colluvial gravel intake and pastoral occupation layers, anchoring the deposit to radiometric dating and contextualising it against the known regional climatic history. The interpretation of pedostratigraphic evidence highlights subsequent phases of use, abandonment, and repurposing of the canals, reflecting shifts in land-use from agriculture to pastoralism and dynamic adaptation and resilience of the local ancient communities in response to Late-Holocene climate changes and geopolitical events.